Analysis of the Level of Satisfaction of Darwinbox Application Users at PT Nippon Indosari Corpindo Tbk Using the End User Computing Satisfaction (EUCS) Method - Rezania Agramanisti Azdy; Hermawan Kurniansyah Putra (Information Technology and Science (ITScience), 2023)
The Darwinbox Personnel Information System is one of the developments in information technology in the staffing system that is utilized by PT Nippon Indosari Corpindo Tbk to assist the work of its employees in facilitating and assisting in carrying out attendance, applying for leave, changing personal money used for office purposes (reimbursement). The purpose of this study was to determine user satisfaction with the Darwinbox application at PT Nippon Indosari Corpindo Tbk and measurements were carried out using the End User Computing Satisfaction (EUCS) method. This research was conducted at PT Nippon Indosari Corpindo Tbk on 96 respondents. The results of the calculation of the T hypothesis test obtained the value of the Content variable (X1) sig. 0.000, Format (X3) value sig. 0.000, Ease Of Use (X4) sig. 0.000 where the sig. value of 0.05 can be concluded that the independent variable (X) has no partial effect on the dependent variable (Y). Simultaneously Content, Accuracy, Format, Ease Of Use and Timeliness have a significant effect on user satisfaction and have a very strong relationship with user satisfaction with a percentage value of 82.4%.